Mercedes Aguirre and Richard Buxton. Cyclops: The Myth and Its Cultural History. Oxford University Press, 2020, 456 pp, 94 images. ISBN: 9780198713777 - López Fic, Carolina (Amaltea. Journal of Myth Criticism, 2021)
This document is a review of the book Cyclops: The Myth and Its Cultural History, written by Mercedes Aguirre and Richard Buxton. It presents a summary of the book's content and highlights the main arguments put forward by the authors during its development.